2022
DOI: 10.3390/diagnostics12112570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of CALR-Mutant Type and Burden on the Phenotype of Myeloproliferative Neoplasms

Abstract: Somatic CALR mutations occur in approximately 70% of patients with JAK2 V617F-negative essential thrombocythemia (ET) and primary myelofibrosis (PMF). We evaluated the effects of the CALR mutant type and burden on the phenotype of CALR-mutated myeloproliferative neoplasms (MPN). Of the 510 patients with suspected or diagnosed MPN, all 49 patients detected with CALR mutations were diagnosed with ET (n = 32) or PMF (n = 17). The CALR mutant burden was significantly higher in PMF than in ET (45% vs. 34%), and typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
(55 reference statements)
0
4
1
Order By: Relevance
“…Indeed, mutant CALR is accountable for a gain-of-function property, triggering thrombopoietin receptor activation and downstream cellular signalling via the JAK-signal transducer and activator of transcription (JAK-STAT) pathway. Despite all of this evidence, making CALR one of the most important diagnostic markers tested upon diagnosis of a myeloproliferative disorder, our data suggest a milder disease in patients harbouring CALR mutations since it is related to higher platelet counts, lower haemoglobin levels, and leukocyte counts but a lower risk of thrombosis than patients with JAK2 and MPL mutations [31].…”
Section: Discussioncontrasting
confidence: 65%
“…Indeed, mutant CALR is accountable for a gain-of-function property, triggering thrombopoietin receptor activation and downstream cellular signalling via the JAK-signal transducer and activator of transcription (JAK-STAT) pathway. Despite all of this evidence, making CALR one of the most important diagnostic markers tested upon diagnosis of a myeloproliferative disorder, our data suggest a milder disease in patients harbouring CALR mutations since it is related to higher platelet counts, lower haemoglobin levels, and leukocyte counts but a lower risk of thrombosis than patients with JAK2 and MPL mutations [31].…”
Section: Discussioncontrasting
confidence: 65%
“…Notably, Guglielmelli et al recently found an association of high mutant CALR VAF (≥55%) with shorter anemia-free and leukocytosis-free survivals, and thereby, more aggressive disease compared to low CALR VAF (<55%) in a cohort of 620 patients who had PMF or secondary MF [ 75 ]. Interestingly, CALR type 2/type 2-like mutations were associated with higher median Hb levels, significantly higher platelet counts, and higher white blood cell counts compared to CALR type 1/type 1-like mutations in a small cohort of PMF patients [ 76 ]. TP53 mutations were enriched (19%) in patients who had secondary MF and ≥2 cytopenias ( p = 0.0024) [ 11 ].…”
Section: Genes Associated With the Myeloproliferative And Myelodeplet...mentioning
confidence: 99%
“…They have found that in patients with type 1-like CALR mutation, CALR mutant burden was negatively correlated with the hemoglobin level and platelet count, whereas CALR mutant burden was positively correlated with absolute neutrophil count and platelet count with type 2-like CALR-mutated patients. Nevertheless, the study was conducted on a small number of patients (Kim et al, 2022). There are several methods for detecting the CALR mutation.…”
Section: Figurementioning
confidence: 99%